2020
DOI: 10.4038/jm.v15i1.7593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smartphone usage on academic performance: a study on undergraduates in FMSC of University of Sri Jayewardenepura, Sri Lanka

Abstract: This Quantitative study is focused on investigating the impact of smartphone usage on academic performance of the undergraduates in Faculty of Management Studies and Commerce (FMSC) of University of Sri Jayewardenepura, Sri Lanka. Two hundred and twenty two (222) undergraduates who are currently studying in Faculty of Management Studies and Commerce of University of Sri Jayewardenepura were participated as the respondents of this study. Multiple linear regression analysis is used to investigate the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…The research "The impact of smartphone usage on academic performance of the undergraduates." Chathurangaa and Jaysundara [13] revealed that the majority of the respondents have used their smartphones to access social media applications, and the Web-browser is identified as the most frequently used mobile application for the study purposes. There is a positive significant impact of smartphone usage on the academic performance of the respondents in terms of Communicability with fellow students and lecturers, and accessibility to study materials.…”
Section: Introductionmentioning
confidence: 99%
“…The research "The impact of smartphone usage on academic performance of the undergraduates." Chathurangaa and Jaysundara [13] revealed that the majority of the respondents have used their smartphones to access social media applications, and the Web-browser is identified as the most frequently used mobile application for the study purposes. There is a positive significant impact of smartphone usage on the academic performance of the respondents in terms of Communicability with fellow students and lecturers, and accessibility to study materials.…”
Section: Introductionmentioning
confidence: 99%